The Russian financial system in the context of possible cyber attacks - Daroshka Vitali; Fedorova Marina; Aleksandrov Igor; Rasskazova Olga; Parshukov Aleksey; Isakov Alexander (E3S Web of Conferences, 2023)
The fourth industrial revolution is one of the most ambiguous stages in the evolution of the world economy: the basis of its unpredictability is the involvement in the orbit of all the states of the world, regardless of their level of economic and technological development, while the key postulate of Industry 4.0 - information openness and transparency of socio-economic systems - has become the source of the appearance of a new concept of not only managerial, but also military and political thinking of elites. The business model of the digital economy, as the main product of the fourth pro-industrial revolution, is almost all built on extreme parameters: on the one hand, there is a pronounced motivation for the "availability of personal data and the active development of institutions of digital commonwealth of countries, encouragement for cross-border digital commonwealth and association, on the other hand, today there is a growing separatist sentiment and deinternationalization of countries due to a "domino effect" in the world economic system, in which the countries most involved in the digital dialogue become victims of their own openness and blind adherence to the ideals of scientific and technological progress. The specified contradictions of key ideas of digital economy are the basis of scientific research of national security of financial system of the Russian Federation taking into account escalation of military-political and economic tension in the international dialogue with EU and USA and difficult to predict scenarios of further developments.